Preferences for working in rural clinics among trainee health professionals in Uganda: a discrete choice experiment - Rockers Peter C; Jaskiewicz Wanda; Wurts Laura; Kruk Margaret E; Mgomella George S; Ntalazi Francis; Tulenko Kate (BMC, 2012)
Abstract Background Health facilities require teams of health workers with complementary skills and responsibilities to efficiently provide quality care. In low-income countries, failure to attract and retain health workers in rural areas reduces population access to health services and undermines facility performance, resulting in poor health outcomes. It is important that governments consider health worker preferences in crafting policies to address attraction and retention in underserved areas. Methods We investigated preferences for job characteristics among final year medical, nursing, pharmacy, and laboratory students at select universities in Uganda. Participants were administered a cadre-specific discrete choice experiment that elicited preferences for attributes of potential job postings they were likely to pursue after graduation. Job attributes included salary, facility quality, housing, length of commitment, manager support, training tuition, and dual practice opportunities. Mixed logit models were used to estimate stated preferences for these attributes. Results Data were collected from 246 medical students, 132 nursing students, 50 pharmacy students and 57 laboratory students. For all student-groups, choice of job posting was strongly influenced by salary, facility quality and manager support, relative to other attributes. For medical and laboratory students, tuition support for future training was also important, while pharmacy students valued opportunities for dual practice. Conclusions In Uganda, financial and non-financial incentives may be effective in attracting health workers to underserved areas. Our findings contribute to mounting evidence that salary is not the only important factor health workers consider when deciding where to work. Better quality facilities and supportive managers were important to all students. Similarities in preferences for these factors suggest that team-based, facility-level strategies for attracting health workers may be appropriate. Improving facility quality and training managers to be more supportive of facility staff may be particularly cost-effective, as investments are borne once while benefits accrue to a range of health workers at the facility.